(untitled) (Journal of Advanced Veterinary and Animal Research, 2014)
NOTE: On 05/01/2015 The first author, Ozkan Simsek, was added to the website. This author was already on the PDF. The purpose of the present study was to determine the changes in selected hematology and serum biochemistry of Angora cats (Felis catus) during growth period. A total of 32 Angora cats (16 adults and 16 kittens) were used in this study. Blood samples were collected from the animals, and were analyzed for white blood cells, red blood cells, hemoglobin, packed cell volume, mean corpuscular volume (MCV), mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, granulocytes, monocytes and lymphocytes numbers. In the serum, alanine aminotransferase, aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma glutamyl transferase (GGT), lactate dehydrogenase (LDH), creatinine kinase (CK), total cholesterol, glucose, triglyceride, urea, creatinine, total protein, albumin, Ca, Mg, Pi levels were determined. Monocyte level was found higher, and ALP, LDH, CK activities and Pi levels were lower in adult cats as compared to the kittens. MCV was lower and GGT and AST activities, and glucose level were higher in kittens of 1.5-3 months old than in kittens of >3 months. Concentrations of total cholesterol and Mg were higher in kitten (1.5-3 months old) than in adult cats. In conclusion, age related effects on hematological and biochemical blood parameters have been determined for the first time in Angora cats. http://dx.doi.org/10.5455/javar.2015.b42